Development of Augmented Reality Learning Media on IPAS Subject Matter of the Respiratory System - Hanik Puji Rahayu; Desi Wulandari (Jurnal Penelitian Pendidikan IPA, 2024)
The lack of use of learning tools in science and science lesson content regarding the respiratory system in class V elementary school makes students quickly feel bored. This results in students not understanding what has been conveyed by the teacher. This investigation aims to develop augmented reality learning media for science and science lesson content on the respiratory system for class V elementary schools. This type of research is Research and Development (R&D) which refers to the Borg and Gall theory with ten stages. The data collection techniques used in this research were observation, question and answer, and questionnaires. Based on the data analysis carried out, the following results were obtained. The results of the material expert validation test were 81.60% which was included in the very feasible group; The results of the media expert validation test were 96.60% which was included in the very feasible group. Apart from that, scores were obtained before and after the use of the learning media developed. As seen from the results of these values, the media developed is declared effective if used as a learning tool in the science and science learning content regarding the respiratory system. So, it can be concluded that the tools developed are suitable and effective for use in the learning process.